The Impact of Goodwill Recognition and Goodwill Impairment on the Increasing Holdings of Block Shareholders. (23rd November 2021) - Tan, Xiaofang; Ge, Xin; Liu, Qinghua; Yuan, Zhengjun
Abstract : There is a large amount of goodwill recognition and goodwill impairment. These characteristics would trigger stock price fluctuation. Hence, stakeholders will increase holdings to mitigate the volatility of stock prices. According to the data in regard to the Chinese A-share nonfinancial listed companies from 2007 to 2020, we study the reaction of block shareholders after goodwill recognition and goodwill impairment, respectively. Our findings are as follows: (1) goodwill recognition leads to increasing holdings of block shareholders; (2) goodwill impairment also leads to increasing holdings of block shareholders when there is a large amount of goodwill impairment. We also take state ownership into consideration: compared to state-owned firms, private firms show a much stronger positive relation between goodwill recognition and level of increasing holdings of block shareholders, but there is no significant relation between goodwill impairment and increasing holdings of block shareholders in state-owned firms. These empirical results provide us with abundant evidence that block shareholders would increase shareholdings when there is goodwill recognition due to private information of positive future expectation in M&A. Meanwhile, block shareholders would stabilize stock price via increasing shareholdings when goodwill is impaired.